PENYULUHAN FUNGSI KOGNITIF PADA LANSIA - Yudhisman Imran; Irmiya Rachmiyani; Donna Adriani; Mustika Anggiane Putri; Patwa Amani; Dimas Jordhi (CV. Multi Kreasi Media, 2023)
Cognition is the highest function of the brain. Impaired cognitive function in the long term and not treated adequately can interfere with daily activities such as senile dementia or dementia. Before a person develops dementia, there is a transitional condition between healthy old age and dementia called Mild Cognitive Impairment. This condition occurs as a result of a degenerative process called Mild Cognitive Impairment (MCI) or is caused by vascular disorders, namely Vascular Cognitive Impairment (VCI). MCI in the future can develop into dementia over a period of 5-6 years. Cognitive function consists of several domains, namely: attention, working memory, episodic memory, verbal learning, executive function, and visuospatial. Cognitive function can decrease due to age, or due to brain injury such as head trauma, stroke, and even degenerative diseases such as hypertension and diabetes mellitus. The importance of controlling vascular risk factors can slow the decline in cognitive function. This counseling is carried out as an educational effort to the community to increase knowledge about cognitive function, risk factors, and efforts to prevent cognitive decline. Cognitive function counseling for the elderly has been carried out through zoom meeting to residents of Duren Sawit RT 002/04.